Assessing Cerebral Glucose Metabolism in Patients with Idiopathic Rapid Eye Movement Sleep Behavior Disorder. Issue 12 (December 2015) - Ge, Jingjie; Wu, Ping; Peng, Shichun; Yu, Huan; Zhang, Huiwei; Guan, Yihui; Eidelberg, David; Zuo, Chuantao; Ma, Yilong; Wang, Jian
Idiopathic rapid eye movement sleep behavior disorder (RBD) is a risk marker for subsequent development of neurodegenerative parkinsonism. In this study, we aimed to investigate whether regional cerebral metabolism is altered in patients with RBD and whether regional metabolic activities are associated with clinical measurements in individual patients. Twenty-one patients with polysomnogram-confirmed RBD and 21 age-matched healthy controls were recruited to undertake positron emission tomography imaging with [ 18 F]fluorodeoxyglucose. Differences in normalized regional metabolism and correlations between metabolic activity and clinical indices in RBD patients were evaluated on a voxel basis using statistic parametric mapping analysis. Compared with controls, patients with RBD showed increased metabolism in the hippocampus/parahippocampus, cingulate, supplementary motor area, and pons, but decreased metabolism in the occipital cortex/lingual gyrus ( P < 0.001). RBD duration correlated with metabolism positively in the anterior vermis ( r =0.55, P = 0.01), but negatively in the medial frontal gyrus ( r =-0.59, P = 0.005). In addition, chin electromyographic activity presented a positive metabolic correlation in the hippocampus/parahippocampus ( r =0.48, P = 0.02), but a negative metabolic correlation in the posterior cingulate ( r =-0.61, P = 0.002). This study has suggested that region-specific metabolic abnormalities exist in RBD patients and regional metabolic activities are associated with clinical measures such as RBD duration and chin electromyographic activity.